Tunnel Intergrowth LixMnO2 Nanosheet Arrays as 3D Cathode for High‐Performance All‐Solid‐State Thin Film Lithium Microbatteries - Xia, Qiuying; Zhang, Qinghua; Sun, Shuo; Hussain, Fiaz; Zhang, Chunchen; Zhu, Xiaohui; Meng, Fanqi; Liu, Kaiming; Geng, Hao; Xu, Jing; Zan, Feng; Wang, Peng; et al. (Advanced materials (Weinheim), 2021)
All‐solid‐state thin film lithium batteries (TFBs) are proposed as the ideal power sources for microelectronic devices. However, the high‐temperature (>500 °C) annealing process of cathode films, such as LiCoO2 and LiMn2O4, restricts the on‐chip integration and potential applications of TFBs. Herein, tunnel structured LixMnO2 nanosheet arrays are fabricated as 3D cathode for TFBs by a facile electrolyte Li+ ion infusion method at very low temperature of 180 °C. Featuring an interesting tunnel intergrowth structure consisting of alternating 1 × 3 and 1 × 2 tunnels, the LixMnO2 cathode shows high specific capacity with good structural stability between 2.0 and 4.3 V (vs. Li+/Li). By utilizing the 3D LixMnO2 cathode, all‐solid‐state LixMnO2/LiPON/Li TFB (3DLMO‐TFB) has been successfully constructed with prominent advantages of greatly enriched cathode/electrolyte interface and shortened Li+ diffusion length in the 3D structure. Consequently, the 3DLMO‐TFB device exhibits large specific capacity (185 mAh g−1 at 50 mA g−1), good rate performance, and excellent cycle performance (81.3% capacity retention after 1000 cycles), outperforming the TFBs using spinel LiMn2O4 thin film cathodes fabricated at high temperature. Importantly, the low‐temperature preparation of high‐performance cathode film enables the fabrication of TFBs on various rigid and flexible substrates, which could greatly expand their potential applications in microelectronics. Tunnel intergrowth LixMnO2 nanosheet arrays consisting of alternating 1 × 3 and 1 × 2 tunnels are developed by a facile electrolyte Li+ ion infusion method at a low temperature of 180 °C. Benefiting from the stable tunnel structure for the cathode and favorable architecture with abundant 3D cathode/electrolyte interface, the constructed LixMnO2/LiPON/Li thin‐film battery achieves large specific capacity and outstanding cycle life.